“Child maltreatment” – sexual, physical, and emotional abuse and neglect as potential predictors of suicidal behaviour among adolescents – an acute problem in Poland - Cepuch, Grażyna; Liber, Patrycja; Kruszecka-Krówka, Agnieszka (Medical Studies/Studia Medyczne, 2022)
In the last few decades, the number of suicide attempts and suicides has been growing dynamically, also among young people. Sexual, physical, and psychological abuse and neglect are recognised as risk factors that encourage adolescents to engage in suicidal behaviour. Although suicides are one of the most frequent causes of death, they have failed to become a priority in the area of public health. The purpose of this paper is to present selected predictors of suicidal behaviour based on an analysis of scientific findings in the area of suicidology, and to increase the awareness of the medical personnel of general paediatric clinics and other (including non-medical) professionals working with children, youths, and families about suicide risks in this particular social group. Suicide prevention should become one of the basic health care services, also in relation to paediatric care.